High Comorbidity in Premature Infant: Abdominal Aortic Thrombosis, Wolff-Parkinson-White Syndrome, Secondary Hypothyroidism - Alena S. Tikhonova; Anastasiya M. Kozlova; Anna A. Tsaturova (Union of pediatricians of Russia, 2023)
Background. Neonatal thromboses, both venous and arterial, are a rare pathology, and experience in systemic thrombolysis is very low. Thus, the methods of adult management are currently being adapted to pediatric practice.Clinical case description. This report describes clinical case of abdominal aortic thrombosis in a premature infant with later diagnosed Wolff-ParkinsonWhite syndrome and acquired hypothyroidism developed due to antiarrhythmic therapy.Conclusion. The premature boy had high comorbidity that required many specialists' involvement. Timely systemic thrombolytic therapy and antiarrhythmic drugs selection made it possible to save the child's life and most likely to avoid disability in the future.